Influence of Exogenous Fertilizer Application on Growth of Calamus thwaitesii Becc. and Hook. f. at Nursery Stage - R, Divya; B. N, Sathish; C, Dhanush; M. N., Ashwath; K. P, Vijayalakshmi; C. V., Gajendra (International Journal of Bio-resource and Stress Management, 2022)
The present investigation was carried out at Sampaje Forest Nursery, Karnataka State Forest Department, Kodagu district, Karnataka, India during 2017. The study aimed at understanding the effect of conventional (organic and inorganic fertilizers) and bio-fertilizers on the growth rate of the Calamus thwaitesii seedlings in the nursery stage. Different dosages of fertilizers, such as Vermicompost, Pongamia cake, Di-Ammonium Phosphate (DAP), Muriate of Potash (MOP), Azospirillum, Micorrhiza, Bassilus mucilaginous (KSB)and Bassilus megatherium (P SB) was applied to five-month-old seedling at the nursery stage and growth parameters were recorded at 30 days interval till 150 days. The results revealed that 1.5 g of Di-Ammonium Phosphate with 1.5 g of Muriate of Potash at 150 days interval showed the best result for shoot height (53.85 cm), collar diameter (14.81 mm), number of leaves (8) and fresh root and shoot weight (11.5 g and 23.8 g respectively). Among the bio-fertilizers the highest volume index value (9521.62 cm3) was observed in for KSB (10 g) +Mycorrhizal culture (10 g) followed by Azospirillum (10 g) +PSB (10 g) +Mycorrhizal culture (10 g) (9287.20 cm3). The Phosphate and Potassium rich fertilizers or phosphate and potassium solubilizing bacteria were found to enhance the growth of Calamus thwaitesii seedlingsin the nursery stage.